Proposal of an environmental performance index to assess leather-manufacturing companies - Rebelato, Marcelo Girotto [UNESP]; Rodrigues, Andréia Marize [UNESP]; Ferreira, Bruna Sousa [UNESP] (Elsevier, 2024)
Despite the global economic and environmental importance of the leather industry, the specialized literature still presents an important gap in analyzing the environmental performance of the leather manufacturing process from the waste generated. This paper aims to propose an unprecedented index (Index of Leather Manufacturing- ILM) to evaluate the environmental performance of leather manufacturing processes. The development of the index combines Life Cycle Assessment (LCA) and a Multicriteria Decision Method (MCDM) and is oriented to consider the impact of waste on environmental health. Its estimate is based on: the calculation of the environmental potential impact of the waste; the waste quantity produced by the company over a given period; the relative geographic coverage that each waste can achieve; the assessment of the appropriateness of the disposal of waste generated by the firm. The proposed index was tested on a large Brazilian leather manufacturer. The results showed that the waste management in the company is not perfect but is well rated, and residues with the greatest environmental impact are: wetblue shavings, wetblue sawdust, and gaseous emissions from beam house operation.
Keywords: Environmental impacts; Environmental indicators; Environmental performance; Environmental toxicity potential; Tannery industry